Ensuring sustainable development of the metallurgical industry of the republic of belarus under sanctions in 2022 - N. A. Romashko; V. A. Chaus (Литьë и металлургия)
The article considers the results of OJSC “BSW – Management Company of Holding “BMC”, the largest metallurgical enterprise in the Republic of Belarus in 2022. It also presents market diversification and export orientation towards friendly markets. The article describes new types of products and achievements in the field of quality, as well as the functional and operational work of the enterprise’s personnel.